The Effect of Health Education on Improving Pregnant Women’s Knowledge: A Pre-Experimental Study - Ita Haryanti; Wachyu Amelia (CV. AFDIFAL MAJU BERKAH, 2026)
Pregnant women’s knowledge of pregnancy danger signs is an important factor in preventing complications and reducing the risk of maternal morbidity and mortality. A lack of understanding of these danger signs often leads to delays in seeking medical care. This study aimed to determine the effect of health education on improving pregnant women’s knowledge of pregnancy danger signs in the working area of Sekarjaya Public Health Center in 2025. This study employed a pre-experimental design using a one-group pretest–posttest approach and involved 30 respondents selected through purposive sampling. Data were collected using a structured questionnaire consisting of 15 multiple-choice questions that had been tested for validity and reliability. The intervention consisted of health education on pregnancy danger signs, delivered for approximately 45 minutes using lectures, interactive discussions, question-and-answer sessions, and leaflet media. Data analysis using the Paired t-Test showed a significant increase in knowledge scores, from a mean of 63.47 before the intervention to 82.20 after the intervention (p = 0.000). The results indicate that health education is effective in improving pregnant women’s knowledge of pregnancy danger signs. It is recommended that health workers integrate health education as an essential component of antenatal care services to enhance maternal preparedness and safety during pregnancy.